2018
DOI: 10.3390/nu10091327
|View full text |Cite
|
Sign up to set email alerts
|

Hairless Canaryseed: A Novel Cereal with Health Promoting Potential

Abstract: Glabrous canaryseeds were recently approved for human consumption as a novel cereal grain in Canada and the United States. Previously, canaryseeds were exclusively used as birdseed due to the presence of carcinogenic silica fibers; therefore the nutritional value of the seeds has been seriously overlooked. Two cultivars of glabrous canaryseeds (yellow and brown) were created from the hairy varieties. They are high in protein compared to other cereal grains, and contain high amounts of tryptophan, an amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 87 publications
(117 reference statements)
0
24
0
Order By: Relevance
“…The hairless canary seed was recently approved as a novel food by Health Canada and received GRAS status from the US FDA. Previous research has shown its potential as a whole‐grain food ingredient (Mason et al, ; Patterson et al, ) and a promising source of small starch granules and plant protein (Abdel‐Aal & Hucl, ; Abdel‐Aal et al, , ; Irani et al, ). The current study demonstrates better stability for hairless canary seed starch gels over wheat starch gel during refrigerated storage and freeze–thaw treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hairless canary seed was recently approved as a novel food by Health Canada and received GRAS status from the US FDA. Previous research has shown its potential as a whole‐grain food ingredient (Mason et al, ; Patterson et al, ) and a promising source of small starch granules and plant protein (Abdel‐Aal & Hucl, ; Abdel‐Aal et al, , ; Irani et al, ). The current study demonstrates better stability for hairless canary seed starch gels over wheat starch gel during refrigerated storage and freeze–thaw treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium chloride, sucrose, and xanthan gum are usually used in food formulations, particularly in baked products to improve flavor, taste, texture, and color. Recently, two reports have shown the potential of hairless canary seed as a food ingredient in many food applications including baked goods and baking mixes (Mason, L’Hocine, Achouri, & Karboune, ; Patterson et al, ). Salts can result in either increase or decrease in the rate of starch gelatinization, gelation, and retrogradation subject to their type and concentration (Chiotelli, Pilosio, & La Meste, ; Wang, Zhou, Yang, & Cui, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Buckwheat is almost exclusively sold as dehulled grouts and flour produced from dehulled groats. Canary seed's potential in the human diet has been elucidated thus far for dehulled groats also (Abdel-Aal et al, 2011;Mason et al, 2018), while broomcorn millet is occasionally sold as white flour. The additional processing steps reduced the mineral nutrient content in dehusked buckwheat grains as observed similarly in the major cereals (Oghbaei and Prakash, 2013;Pandey et al, 2015).…”
Section: Promises and Potential For Developing Underutilized (Pseudo)mentioning
confidence: 99%
“…A recent addition to the cereal group is canaryseed (Phalaris canariensis L.), which is a true cereal belonging to the family Poaceae. Canaryseed contains ~19%-23% protein (Mason et al, 2018;Patterson et al, 2018) which is higher than that of other cereals, or pseudocereals, commonly available in the market (Bekkering & Tian, 2019;Patterson et al, 2018). Canada, especially the province of Saskatchewan, is the leading producer and exporter of canaryseed in the world (Patterson et al, 2018;Canaryseed Development Commission of Saskatchewan, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…However, hairless (glabrous) canaryseed varieties, devoid of siliceous trichomes (hairs) that are toxic to human beings, were recently approved by the US Food and Drug Administration Agency and Health Canada for human consumption (Health Canada, 2016;Patterson et al, 2018). The higher protein content, potential to produce bioactive peptides and gluten-free nature, provides potential for the increased use of canaryseed in the food industry (Mason et al, 2018) as a plant protein source over other conventional cereal grains.…”
Section: Introductionmentioning
confidence: 99%